Perceptions of family-of-origin belief systems among men in treatment for sexual offending: A phenomenological investigation - Huebner, Jessie (Journal of addictions & offender counseling, 2024)
Sexual offending is a public concern and results in lasting detrimental effects. Despite evidence demonstrating the impact of belief systems on sexual offending behaviors, research exploring family belief systems among individuals who perpetrate sexual offenses is limited. This qualitative study explored the lived experiences of 10 cisgender men in outpatient treatment for sexual offending. Following Interpretative Phenomenological Analysis (IPA), findings indicated a broad range of early experiences for men who have sexually offended. The rich findings that emerged from the lived experiences of the participants are presented in relation to current knowledge, and practice implications are shared.